The cost-effectiveness of implementing HPV testing for cervical cancer screening in El Salvador - Campos, Nicole G. (Int J Gynaecol Obstet, 2019)
OBJECTIVE: To assess the cost-effectiveness of HPV-based screening and management algorithms for HPV-positive women in phase 2 of the Cervical Cancer Prevention in El Salvador (CAPE) demonstration, relative to the status quo of Pap-based screening. METHODS: Data from phase 2 of the CAPE demonstration (n=8000 women) were used to inform a mathematical model of HPV infection and cervical cancer. The model was used to project the lifetime health and economic outcomes of HPV testing every 5 years (age 30–65 years), with referral to colposcopy for HPV-positive women; HPV testing every 5 years (age 30-65 years), with immediate cryotherapy for eligible HPV-positive women; and Pap testing every 2 years (age 20–65 years), with referral to colposcopy for Pap-positive women. RESULTS: Despite slight decreases in the proportion of HPV-positive women who received treatment relative to phase 1, the health impact of screening in phase 2 remained stable, reducing cancer risk by 58.5%. As in phase 1, HPV testing followed by cryotherapy for eligible HPV-positive women remained the least costly and most effective strategy (US$490 per year of life saved). CONCLUSION: HPV-based screening followed by immediate cryotherapy in all eligible women would be very cost-effective in El Salvador.